A possible role of urinary genotoxic Escherichia coli in prostate cancer in Nigerian patients - Sharon O. Akinpelu; Grace I. Olasehinde; Olayemi O. Akinnola (BMC Research Notes)
Abstract Objective Infection and inflammation are potential initiating factors for the development and progression of prostate cancer. This study investigated the presence of bacterial genotoxins; colibactin (clb) and cytolethal distending toxin (cdt) in Escherichia coli isolated from urine samples of individuals diagnosed with prostate cancer as well as those with benign prostatic hyperplasia. E. coli was isolated from urine samples from prostate cancer patients (cases, n = 30) and men with benign prostate hyperplasia (controls, n = 40). The presence of colibactin (clb) and cytolethal distending toxin (cdt) genes was evaluated in E. coli isolates using polymerase chain reaction. Results The frequency of E. coli was 36.0% of prostate cancer patients and 30.0% of controls, respectively (p = 0.557). Furthermore, there was a higher occurrence of the clb gene in cases compared to controls (36.4% vs. 8.3%). Cytolethal distending toxin (cdt) gene was absent in all isolates examined. The analysis revealed no significant relationship between the selected genotoxins and prostate cancer (p = 0.104). The Gleason grade of the cancer was not a major determinant in the occurrence of clb within the cancer cases. The present study is the first report investigating bacterial genotoxins in urine samples of Nigerian prostate cancer patients. Our findings showed no association between bacterial genotoxins and prostate cancer. Additional investigations are warranted to further investigate the role of bacterial genotoxins in prostate cancer development.